The Effect of Mirror Therapy on Exterm Muscle Strength in Non-Hemorrhagic Stroke Patients Based on Self Care Theory - Siti Robi’atus Sholiha; R. Khairiyatul Afiyah; Hotimah Masdan Salim; Abdul Muhith; Siti Nur Hasina (Universitas STRADA Indonesia, 2025)
Background: Non-hemorrhagic strokes result in neuromuscular disorders with reduced activity and weakness in joint movement and even disability. This condition receives treatment at the hospital in the form of educational therapy, diet, medication and ROM (active and passive). Purpose: The aim of the research was to determine the effect of Mirror Therapy on extremity muscle strength in non-hemorrhagic stroke patients based on self-care theory. Methods: Quasi experiment research design with a pretest posttest approach with control group design. The population of all non-hemorrhagic stroke patients with a sample size of 40 people, divided into 2 groups, namely the control group and the intervention group, was selected using a purposive sampling technique. The instruments used in this research include respondent characteristics, MMT (Manual Muscle Testing) observation sheets and Mirror Therapy SOP. Data analysis used the Mann Whitney U-test with a significance value of P value < 0.05. Results: The results of the study showed that the average muscle strength score in the Mirror Therapy intervention group was 1.55 before and after 2.65, while in the control group with standard hospital treatment before 1,40 and after 1.95. The Wilcoxon Test results show P value = 0.000 in the intervention group and P value = 0.000 in the control group, meaning there is an increase in extremity muscle strength in the intervention and control groups. Based on the Mann Whitney test, it shows P value = 0.013, meaning there is no differences in Mirror Therapy on extremity muscle strength in non-hemorrhagic stroke patients. Conclusion: The application of Mirror Therapy affects the level of extremity muscle strength in non-haemorrhagic stroke patients. Nurses are expected to be able to apply Mirror Therapy to apply it in nursing practice.